Contributes and challenges of problem-based learning in medical training (Research, Society and Development, 2020)
The objective of this study is to reflect on medical education from the perspective of an integrated and contextualized teaching practice using the Problem Based Learning (PBL) methodology. For this purpose, in the methodological field, the exploratory research of qualitative approach was adopted, making use of the bibliographical and documentary researches for the theoretical basis and exploration of the theme. For data discussion and analysis, the Content Analysis method was adopted. The results indicated that it is necessary to rethink medical education in a dialogic, humanized and critical perspective, observing the need for integration of theory and practice and that PBL can contribute to the improvement of the educational process and the development of positive skills and attitudes by students, reflecting on professional practice.